Which Stock Market Index Performed Positively During The Covid-19 Outbreak?: From Economic Perspective With Differential Test Analysis - Girang Permata Gusti; Rudi Triadi Yuliarto; Novira Kusrini (AIBPM Publisher, 2021)
The purpose of this study is to research the world's major stock indexes that have performed positively during the COVID-19 outbreak. This study uses a quantitative method using different test analyses, by comparing the typical stock market index prices from January to August 2019, 2020, and 2021. The research sample used is 45 major world stock indices, with the source of compiling and collecting data on the investing.com website. The results showed that the stock indexes of US NASDAQ Composite (IXIC), Denmark (OMX Copenhagen 25), New Zealand (Dow Jones New Zealand), Russia (MOEX), Taiwan (Taiwan Weighted), and Turkey BIST 100 (XU100) had a positive impact and significantly during the COVID-19 outbreak. Countries that have a quick response in dealing with Covid-19, will have better preparations to prevent deaths and economic downturn, than countries that underestimate this outbreak.